THE INFLUENCE OF PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS ON FINTECH USER LOYALTY MODERATED BY TRUST - Afrian, Yossy; Setijaningsih, Herlin Tundjung (Graduate Program of Universitas Tarumanagara, 2025)
The rapid growth of financial technology (fintech) in Indonesia has changed the landscape of financial services, particularly among younger generations, with 78% of Millennials and Gen Z using fintech applications daily. However, retaining customer loyalty remains a challenge due to growing competition and concerns about security, privacy, and reliability. This study looks at how perceived ease of use, perceived usefulness, and trust affect Fintech user loyalty in Indonesia. This study examines the influence of perceived ease of use, perceived usefulness, and trust on Fintech user loyalty in Indonesia. A quantitative research method was used, using a structured questionnaire that was distributed online to 121 active Fintech payment services users. SmartPLS 4.0 software was used for Partial Least Squares-Structural Equation Modeling (PLS-SEM) to analyze data. The results show that while perceived usefulness greatly increases loyalty, perceived ease of use has a positive but insignificant effect on Fintech user loyalty. As expected, trust has no moderating effect on the association between these parameters and user loyalty, indicating that loyalty is shaped independently by them. These results highlight the importance of perceived usefulness in fostering Fintech user loyalty and emphasize the need for providers to focus on delivering tangible benefits to enhance user retention. Future studies should broaden the demographic focus and investigate other factors affecting user behavior in order to offer more comprehensive insights into Fintech uptake and loyalty.